Find h ( x ) h(x)

Algebra Level 2

Test your basic mathematical skills.

If F ( x ) = x 2 + 2 x 2 F(x) = \dfrac{x^2 +2} {x^2} and F ( h ( x ) ) = x F(h(x)) = x , what is the value of h ( 3 ) h(3) ?

3 3 2 \sqrt 2 ± 1 \pm 1 1 1 1 -1

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Naren Bhandari
Feb 12, 2018

Since F ( x ) = x 2 + 1 x 2 F ( h ( x ) ) = ( h ( x ) ) 2 + 2 ( h ( x ) ) 2 x ( h ( x ) ) 2 ( h ( x ) ) 2 = 2 h ( x ) = 2 x 1 h ( 3 ) = ± 1 \begin{aligned} \ & F(x) = \frac{x^2+1}{x^2} \\& \implies F(h(x)) = \frac{(h(x))^2+2}{(h(x))^2} \\&\implies x(h(x))^2 - (h(x))^2 =2 \\ & \implies h(x) = \sqrt{\frac{2}{x-1}} \\& \implies h(3) = \pm 1\end{aligned}

Blan Morrison
Feb 12, 2018

To make things simpler, let y = h ( x ) y=h(x) . Since F ( h ( x ) ) = x F(h(x))=x , we set up an equation by substituting h ( x ) ( or y ) h(x)~(\text{or}~y) for x x , and setting the whole thing equal to x x : y 2 + 2 y 2 = x \frac{y^2+2}{y^2}=x So we need to solve for y y to get the function. Then, we can plug 3 in. In order for the first step to occur, we should simplify the fraction: 1 + 2 y 2 = x 1+\frac{2}{y^2}=x Then, we subtract 1 from both sides and multiply by y 2 y^2 : 2 = y 2 ( x 1 ) 2=y^2(x-1) The steps are quite obvious from here: 2 x 1 = y 2 \frac{2}{x-1}=y^2 y = ± 2 x 1 y=\pm\sqrt{\frac{2}{x-1}} Then we plug in 3 for x x and h ( 3 ) h(3) for y y : h ( 3 ) = ± 2 3 1 = ± 1 = ± 1 h(3)=\pm\sqrt{\frac{2}{3-1}}=\pm\sqrt{1}=\boxed{\pm1}

Chew-Seong Cheong
Feb 12, 2018

F ( h ( x ) ) = x Given F ( h ( 3 ) ) = 3 ( h ( 3 ) ) 2 + 2 ( h ( 3 ) ) 2 = 3 ( h ( 3 ) ) 2 + 2 = 3 ( h ( 3 ) ) 2 2 ( h ( 3 ) ) 2 = 2 ( h ( 3 ) ) 2 = 1 h ( 3 ) = ± 1 \begin{aligned} F(h(x)) & = x & \small \color{#3D99F6} \text{Given} \\ \implies F(h(3)) & = 3 \\ \implies \frac {(h(3))^2+2}{(h(3))^2} & = 3 \\ (h(3))^2 + 2 & = 3(h(3))^2 \\ 2(h(3))^2 & = 2 \\ (h(3))^2 & = 1 \\ \implies h(3) & = \boxed{\pm 1} \end{aligned}

Ossama Ismail
Feb 12, 2018

F ( h ( x ) ) = x h ( x ) is the inverse of F ( x ) F(h(x)) = x \implies h(x) \ \ \text {is the inverse of } \ \ F(x)

Given that F ( x ) = x 2 + 2 x 2 = Y then x = ± 2 Y 1 \text{Given that} \ \ F(x) = \dfrac{x^2 +2} {x^2} = Y \ \ \ \text {then} \ \ x =\pm \sqrt{\dfrac {2}{Y-1}}

Or h ( x ) = ± 2 x 1 and h ( 3 ) = ± 1 \text{Or} \ \ h(x) = \pm \sqrt{\dfrac {2}{x-1}} \ \ \text{ and} \ \ h(3) = \pm 1

The same I notice that h ( x ) h(x) has to be the inverse of it as f ( h ( x ) ) = x f(h(x)) = x .

Naren Bhandari - 3 years, 3 months ago

There is a lack of quantifier IMHO. $F(h(x))=x$ can't be true for $x \leq 0$ since $F(x)= \frac{x^2+2}{x^2}$>0. So $h(3)=1$. Or maybe we are in $mathbb{C}$.

Garance Buretey - 3 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...